Potensi Perempuan Aceh dalam Pendidikan - Dicky Wirianto (LPPM IAIN Parepare, 2020)
Historically the Acehnese women play an important roles either as leaders, commandos of wars, experts of cultures or other sorts of leaders. Post conflict, tsunami, and peace in Aceh, women in Aceh continue to play an important role in various fields of government, politics, culture, and education. These roles have been preserved until now with different patterns and models. This research is aimed to find out the potential of Acehnese women especially in education fields relating to their roles and functions. The results of this research found that Acehnese women have a big power in education fields. Evidently there are many Acehnese women who have access to become teachers, lecturers, and even professors. More ever they have more quantity to access it. Furthermore, this situation is also supported by the current Qanun in Aceh concerning the protection and empowerment of women. It can be concluded that the culture of Aceh have put the equality level among girls and boys to access the education based on their passion in it.